Endoscopic Management of the Difficult Bile Duct Stones: A Single Tertiary Center Experience - Bülent Ödemiş; Ufuk Barış Kuzu; Erkin Öztaş; Fatih Saygılı; Nuretdin Suna; Orhan Coskun; Adem Aksoy; Zeliha Sırtaş; Derya Arı; Yener Akpınar (Gastroenterology Research and Practice)
Background. Most common bile duct (CBD) stones can be removed with standard techniques using endoscopic retrograde cholangiopancreatography (ERCP), but in some cases additional methods are needed. In this study we aimed to investigate the management of patients with difficult stones and the factors that affect the outcome of patients that have undergone periodic endobiliary stenting. Materials and Methods. Data of 1529 patients with naive papilla who had undergone ERCP with an indication of CBD stones was evaluated retrospectively. Stones that could not be removed with standard techniques were defined as “difficult stones.” Cholangiograms of patients who had difficult stones were revised prospectively. Results. Two hundred and eight patients (13.6%) had difficult stones; 150 of these patients were followed up with periodic endobiliary stenting and successful biliary clearance was achieved in 85.3% of them. Both CBD (p<0.001) and largest stone size (p<0.001) were observed to be significantly reduced between the first and the last procedure. This difference was even more significant in successfully treated patients. Conclusions. Periodic endobiliary stenting can be used as an effective treatment for patients with difficult stones. Sizes of the CBD and of the largest stone are independent risk factors that affect the success rate.